Heterogeneity of CD4+CD25+Foxp3+Treg TCR β CDR3 Repertoire Based on the Differences of Symbiotic Microorganisms in the Gut of Mice - Li, Jun; Xue, Huaijuan; Ma, Qingqing; He, Xiaoyan; Ma, Long; Shi, Bin; Sun, Suhong; Yao, Xinsheng (Frontiers in Cell and Developmental Biology, 2020)
Gut microbes play a crucial role in the occurrence and development of autoimmune diseases. The diversity of intestinal microorganisms affected by the living environment, regulate the immune function of peripheral immune organs and local tissues. In the study, the diversity of intestinal microorganisms of Germ-free (GF), Specific Pathogen-free (SPF), and Clean (CL) BALB/c mice were conducted by 16S rDNA sequencing. High-throughput sequencing technology was used to analysis the composition and characterization of TCR β chain CDR3 repertoires in Regulatory T cells (Treg) in intestine and spleen of GF, SPF, and CL mice, so as to investigate the effects of differential composition of intestinal microorganisms on the CD4+CD25+Foxp3+Treg TCR β CDR3 repertoire of intestine and spleen. We observed that GF, SPF, and CL mice have different gut microorganism composition, and the abundance and quantity of microorganisms are positively correlated with the level of feeding environment. Interestingly, incomplete structure of spleen and small intestine in GF mice was found. Moreover, a significant difference in the usage of high frequency unique CDR3 amino acid sequences was detected in the intestinal Treg TCRβ CDR3 repertoire among GF, SPF and CL mice, and there were a greater heterogeneity in the usage frequency of TRBV, TRBJ, and TRBV-TRBJ combinations gene segments. However, the effect of different feeding environment on the mice Treg TCRβ CDR3 repertoire of spleen was weak, implying that the different composition of intestinal microbiota may primarily affect the diversity of the local Treg TCRβ CDR3 repertoire and does not alter the overall properties of the circulating immune system. These results provide basic data to further analyze the mechanism of gut microbes regulating the intestinal mucosal immune system.